Consistent temperature dependence of functional response parameters and their use in predicting population abundance. Issue 11 (9th August 2019) - Archer, Louise C.; Sohlström, Esra H.; Gallo, Bruno; Jochum, Malte; Woodward, Guy; Kordas, Rebecca L.; Rall, Björn C.; O'Gorman, Eoin J.
Abstract: Global warming is one of the greatest threats to the persistence of populations: increased metabolic demands should strengthen pairwise species interactions, which could destabilize food webs at the higher organizational levels. Quantifying the temperature dependence of consumer–resource interactions is thus essential for predicting ecological responses to warming. We explored feeding interactions between different predator–prey pairs in controlled‐temperature chambers and in a system of naturally heated streams. We found consistent temperature dependence of attack rates across experimental settings, though the magnitude and activation energy of attack rate were specific to each predator, which varied in mobility and foraging mode. We used these parameters along with metabolic rate measurements to estimate energetic efficiency and population abundance with warming. Energetic efficiency accurately estimated field abundance of a mobile predator that struggled to meet its metabolic demands, but was a poor predictor for a sedentary predator that operated well below its energetic limits. Temperature effects on population abundance may thus be strongly dependent on whether organisms are regulated by their own energy intake or interspecific interactions. Given the widespread use of functional response parameters in ecological modelling, reconciling outcomes from laboratory and field studies increases the confidence and precision with which we can predict warming impacts on natural systems. Abstract : The authors assessed whether species' responses to warming can be reliably estimated from experimental data. They then integrated feeding parameters with energetic modelling to estimate abundance of predators. This allows the authors to predict predator persistence with warming using a mechanistic approach, with responses varying depending on species' traits and feeding ecology.